E2F-Dependent Histone Acetylation and Recruitment of the Tip60 Acetyltransferase Complex to Chromatin in Late G(1) - Taubert, Stefan (American Society for Microbiology, 2004)
E2F proteins can either activate or repress transcription. Following mitogenic stimulation, repressive E2F4-p130-histone deacetylase complexes dissociate from, while activating species (E2F1, -2, and -3) associate with, target promoters. Histones H3 and H4 simultaneously become hyperacetylated, but it remains unclear whether this is a prerequisite or a consequence of E2F binding. Here, we show that activating E2F species are required for hyperacetylation of target chromatin in human cells. Overexpression of a dominant-negative (DN) E2F1 mutant in serum-stimulated T98G cells blocked all E2F binding, H4 acetylation, and, albeit partially, H3 acetylation. Target gene activation and S-phase entry were also blocked by DN E2F1. Conversely, ectopic activation of E2F1 rapidly induced H3 and H4 acetylation, demonstrating a direct role for E2F in these events. E2F1 was previously shown to bind the histone acetyltransferases (HATs) p300/CBP and PCAF/GCN5. In our hands, ectopically expressed E2F1 also bound the unrelated HAT Tip60 and induced recruitment of five subunits of the Tip60 complex (Tip60, TRRAP, p400, Tip48, and Tip49) to target promoters in vivo. Moreover, E2F-dependent recruitment of Tip60 to chromatin occurred in late G(1) following serum stimulation. We speculate that the activities of multiple HAT complexes account for E2F-dependent acetylation, transcription, and S-phase entry.